AN ANALYSIS OF MAXIMS FLOUTING IN â€œTHE JUNGLE BOOKâ€ MOVIE SCRIPT - Ester Hanna BR Sembiring; Imam Ghozali (Universitas Sarjanawiyata Tamansiswa, 2017)
This study is about an analysis of maxims flouting in the movie script of The Jungle Book. The aims of this study are to describe the flouted maxims and to describe the function of the maxims flouting. This study applied discourse analysis. The writers got the data from the movie script and used Griceâ€™s theory called Cooperative Principles with the four types of maxims: maxim of quality, maxim of quantity, maxim of relation, and maxim of manner. The study presented that the most frequently fulfilled is maxim of quality, while least frequently is maxim of relation. Most frequently flouted by the characters is the flouting maxim of quantity, and then least frequent is flouting maxim of quality. The functions of flouting maxims used by the characters of flouting maxims were beneficial to avoid discomfort and to give more explanations (prolixity).